Usability measurement based on interaction pattern : an experimental approach / Siti Zuhra Abu Bakar - Abu Bakar, Siti Zuhra (2006)
This research is about the identification of interaction pattern and its usability measurement in the navigation mechanism. It also aims to identify factors that might affect interaction pattern based on previous study and pre-test questionnaire. In this research, experimental approach was used to be the attribute to the complexity involve in data collection of user behavior. This research used a quantitative method of task analysis and experimental data. The analysis was presented to examine the relationship between factors and interaction pattern on email system. Email system was chosen because there is no support on wider range of user task in email system. Individual differences and task complexity play a role in the navigation and organization strategies of users on the web. Therefore, factors such as task and individual differences may play a role in identifying interaction pattern. Email habits among user measure interaction pattern based on task analysis.